2009
DOI: 10.2478/v10026-009-0027-9
|View full text |Cite
|
Sign up to set email alerts
|

Butyl acrylate/4-acryloyloxy benzophenone copolymers as photoreactive UV-crosslinkable pressure-sensitive adhesives

Abstract: Butyl acrylate/4-acryloyloxy benzophenone copolymers as photoreactive UV-crosslinkable pressure-sensitive adhesives It has previously been shown that copolymers of butyl acrylate with 4-acryloyloxy benzophenone can be used as pressure-sensitive adhesives (PSAs). This paper presents the synthesis and application of a solvent-borne polymer system for the preparation of photoreactive UV-crosslinkable acrylic pressure-sensitive adhesives. Butyl acrylate/benzophenone copolymers with molecular mass in the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Different balances between the liquid-like component and solid-like component can lead to different PSA performances [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different balances between the liquid-like component and solid-like component can lead to different PSA performances [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that high performance PSA must have a proper combinational property of both liquid-like (viscous part) and solid-like (elastic part), and the liquid-like means a low modulus of elasticity and a high dissipation of viscosity, whereas the solid-like means a high modulus of elasticity and a low dissipation [ 8 , 10 ]. Different balances between the liquid-like component and solid-like component can lead to different PSA performances [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation